The link between green taxation and economic growth on CO2 emissions: Fresh evidence from Malaysia - Nanthakumar, Loganathan; Muhammad, Shahbaz; Roshaiza, Taha (2014)
This paper explores how carbon taxation and economic growth affect environment hazards in Malaysia using time series data over the period 1974–2010. We applied cointegration and causality approaches to determine the long-term cointegration and direction of causal relationship between these variables. Based on the results, we found the cointegration relationship between the variables. Furthermore, we noted that although Kuznets׳ theory, i.e. inverted-U shaped curve between economic growth and CO2 emissions is valid for Malaysia, the carbon taxation policy is ineffective to control CO2 emissions. The causality analysis revealed that there is a bidirectional relationship between carbon tax and CO2 emissions. Economic growth Granger causes CO2 emissions and carbon tax Granger causes economic growth. To enhance the awareness concerning pollution issues, governments should rely on alternative instruments that may give benefit to the taxpayers and reduce pollution, which is the pivotal issue to be tackled globally.